2001
DOI: 10.1097/00003072-200109000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Tl-201 Chloride and Tc-99m MIBI Accumulation in Lung Adenocarcinoma in Patients With and Without Distant Metastases

Abstract: Tl-201 chloride SPECT may be more effective than Tc-99m MIBI SPECT for evaluating the distant metastatic potential of primary lung adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
2
1
Order By: Relevance
“…Therefore, our finding (radiotracer activity corresponding to the region of pleural effusion) could be explained by radiotracer uptake by the malignant cells of the effusion, a phenomenon which is widely described previously [7][8][9].…”
Section: Discussionsupporting
confidence: 70%
“…Therefore, our finding (radiotracer activity corresponding to the region of pleural effusion) could be explained by radiotracer uptake by the malignant cells of the effusion, a phenomenon which is widely described previously [7][8][9].…”
Section: Discussionsupporting
confidence: 70%
“…In addition to CT, Tl-201 SPECT has been reported to be useful in the evaluation of mediastinal node involvement in lung cancer. 12 14 In our results, however, the use of Tl-201 SPECT alone in the evaluation of mediastinal node involvement was not favorable. Furthermore, the location of abnormal Tl-201 accumulation was only roughly estimated and could not be evaluated precisely according to the lymph node mapping system.…”
Section: Discussioncontrasting
confidence: 62%
“…Previous studies have been performed to evaluate the accuracy of CT or Tl-201 SPECT in the evaluation of mediastinal node involvement. 3 10,12 14 However, most of these studies demonstrated a diagnostic value of single examination separately, and very little attention has been given to the combined examination with CT, Tl-201 SPECT and serum CEA level. Our results show that the combined examination of mediastinal nodal involvement with CT, Tl-201 SPECT and serum CEA level might increase underestimation, but decrease overestimation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation